PENGARUH RELIGIUSITAS, MORALITAS INDIVIDU, DAN EFEKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN (FRAUD) AKUNTANSI - Ni Kadek Mita; Sang Ayu Putu Arie Indraswarawati (UNHI Press, 2021)
The tendency of accounting fraud is a planned fraud that break the accounting rules, this action can harm other parties and it is a desire to do everything for the benefit of a dishonest way. The purpose of this study are to know religiosity effect, individual morality and the effectiveness of the internal control system on the tendency of accounting fraud ( empirical study on the LPD in Gianyar district ). The population of this study is all staff of LPD in Gianyar district, the number of respondents used was 120 people consisting of the head, cashie, administration/accounting. The method that used for determining sample is purposive sample . From the result of this research, religiosity has a positive and significant effect on the tendency of accounting fraud. Meanwhile, individual morality and the effectiveness of the internal control system have no significant effect on the tendency of accounting fraud.